PENGARUH PEMBERDAYAAN, KEPERCAYAAN DIRI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PD BPR BKK MANDIRAJA KABUPATEN BANJARNEGARA - Risya Alva Risqi Setiawan; Fatwa Zuhaena; Tri Esti Masita (Majalah Imiah Manajemen & Bisnis, 2020)
This research entitled "The Effect of Empowerment, Self Efficacy and Organizational Culture on Employee Performance of PD BPR BKK Mandiraja Banjarnegara Regency". The purpose of this study was to analyze empowerment significantly influence the performance of employees of PD BPR BKK Mandiraja Banjarnegara Regency, to analyze self efficacy significantly influence the performance of employees of PD BPR BKK Mandiraja Banjarnegara Regency and to analyze organizational culture significantly influence the performance of employees of PD BPR BKK Mandiraja Banjarnegara Regency .The analytical tool used in this study is multiple linear regression analysis. From this research it can be concluded: The first hypothesis which states empowerment has a significant effect on the performance of PD BPR BKK Mandiraja employees in Banjarnegara Regency, accepted. This is evidenced by the t test, t count empowerment is greater than t table (4,151> 2,0244). The second hypothesis which states self efficacy has a significant effect on the performance of PD BPR BKK Mandiraja employees in Banjarnegara Regency, is accepted. This is evidenced by the t test, t counts self efficacy greater than t table (2,342> 2,0244). The third hypothesis which states organizational culture has a significant effect on the performance of PD BPR BKK Mandiraja employees in Banjarnegara Regency, is accepted. This is evidenced by the t test, t calculates the organizational culture greater than t table (3,080> 2,0244).